2019
DOI: 10.3390/jcm8010054
|View full text |Cite
|
Sign up to set email alerts
|

Methods Used to Assess the 3D Accuracy of Dental Implant Positions in Computer-Guided Implant Placement: A Review

Abstract: The purpose of this review is to examine various assessment methods in order to compare the accuracy between the virtually planned and clinically achieved implant positions. In this review, comparison methods using pre- and post-operative computed topography (CT) data and digital impressions for definitive prosthesis will be described. The method for the displacement and strain for quantification of the error will also be explored. The difference between the planned and the actual implant placement position in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 15 publications
0
39
0
5
Order By: Relevance
“…Vercruyssen et al proposed the definition of accuracy as "the deviation between the position of the 'planned' and the 'inserted' implant" (33) . Accuracy can be assessed by many (53,58,60) Pre-operative and post-operative impressions are made to fabricate dental casts. The casts are scanned, and software is used to superimpose the two scanned casts and analyze the deviation.…”
Section: Methods For Evaluation Of Accuracy Of Implant Placementmentioning
confidence: 99%
See 2 more Smart Citations
“…Vercruyssen et al proposed the definition of accuracy as "the deviation between the position of the 'planned' and the 'inserted' implant" (33) . Accuracy can be assessed by many (53,58,60) Pre-operative and post-operative impressions are made to fabricate dental casts. The casts are scanned, and software is used to superimpose the two scanned casts and analyze the deviation.…”
Section: Methods For Evaluation Of Accuracy Of Implant Placementmentioning
confidence: 99%
“…Pre-and post-operative CBCT (42,53,58,61,62) -3D model analysis (53) -Image replacing analysis (53) CBCT made before surgery to use in planning dental implant position. After surgery, post-operative CBCT is…”
Section: Methods For Evaluation Of Accuracy Of Implant Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of this CT matching method is that the outline of the postoperative implant could be ambiguous due to the artifacts produced from the titanium implant material. The overall implant contour could be enlarged, making the correct identification of the implant geometry difficult [9]. A different method for examining the accuracy using the optical scan has been described [9].…”
Section: Introductionmentioning
confidence: 99%
“…The overall implant contour could be enlarged, making the correct identification of the implant geometry difficult [9]. A different method for examining the accuracy using the optical scan has been described [9]. Although commonly applied to the accuracy studies, the CT matching method was reported to be less accurate than the CAD/CAM-based measurement method by scanning the abutment placed on the implant with an intraoral scanner [10].…”
Section: Introductionmentioning
confidence: 99%